Uji Adaptasi Beberapa Varietas Tanaman Bawang Putih (Allium sativum L.) di Dataran Rendah Muaro Jambi - Windy Kurniaty; Eliyanti Eliyanti; Aryunis Aryunis (Jurnal Media Pertanian, 2022)
The development of garlic cultivation is currently experiencing a very sharp decline, even some local garlic cultivars are very difficult to find both on farmer's land and in the domestic market. One of the main reasons is the presence of imported garlic whose tuber quality is acknowledged to be better than local garlic bulbs and the price is affordable by consumers. This study aims to test the adaptability of several varieties of lowland garlic in Muaro Jambi. The research was carried out in farmers' gardens located in Mendalo Darat, Jambi Luar Kota from May 2020 to July 2020 with Ultisol soil type and located at an altitude of 0-65 m above sea level. The experiment was arranged in a simple randomized block design (RAK) with garlic varieties as a treatment factor. The varieties treated were: v1 ( lumbu putih from DI Yogyakarta), v2 ( lumbu hijau from Batu Malang), v3 (lumbu kuning from Batu Malang), v4 (sangga sembalun from Sembalun, East Lombok, NTB), v5 (jangkiriah adro from Kerinci-Jambi), and v6 (tawangmangu baru from Tawangmangu, Karanganyar) with 4 replications. The results showed that six local varieties of garlic, namely lumbu putih, lumbu hijau, lumbu kuning, tawamangu baru, sangga sambalun and jangkiriah adro on vegetative growth grew well in Muaro Jambi Regency, Jambi Province. The varieties of lumbu putih and sangga sambalun are able to grow, are bulbous and can form cloves in the lowlands of Muaro Jambi.